TINJAUAN HUBUNGAN KUAT TEKAN DAN LENTUR BETON DENGAN BAHAN TAMBAH SERAT BAJA UNTUK PERKERASAN PAKU - Hermansyah, Hermansyah; Siswanto, Muhammad Fauzie; Saputra, Ashar (Jurnal TAMBORA, 2019)
The Director General of Highways issued the 2010 revision 3 specification concerning minimum flexural strength for rigid pavement of 45 kg/cm2 or approximately 4.5 MPa, but the reality of obtaining such flexural strength should be using  high enough concrete quality and it will incur considerably high cost also. In this study was using a normal concrete method with the purpose of research to know  the relationship of compressive strength and flexural of concrete with the addition of variation of fiber 0%, 0,5%, 0,65% and 0,8% from weight of the concrete mixture. The results from this research showed that the compressive strength and flexure had increased successively in the fiber variation 0%, 0.5% and 0.65% amount 31.23 MPa, 33.06 MPa, 35.23 MPa and 4.58 MPa, 4.75 MPa, 5.04 MPa. It is because the fiber contained in the concrete has a fairly even distribution of fiber and does not have clumping. When variations of fiber above 0.65% such as 0.8% variation in the direction of fiber are difficult to control and at the time of mixing occurs clumping, So the value of compressive strength and flexural of concrete are decreases. The relation of compressive strength and flexural of concrete using a variation of steel fiber to obtain equation fs = 0,1226.fc '+ 0,7173 with value R2 = 0,9915 and α 0,82. The results obtained from the test is a rather good when compared with ACI and SNI T- 15-1991-03 method.